2016
DOI: 10.1016/j.cell.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Protein Stability Reveals Age-Dependent Degradation

Abstract: Do young and old protein molecules have the same probability to be degraded? We addressed this question using metabolic pulse-chase labeling and quantitative mass spectrometry to obtain degradation profiles for thousands of proteins. We find that over 10% of proteins are degraded non-exponentially. Specifically, proteins are less stable in the first few hours of their life and stabilize with age. Degradation profiles are conserved and similar in two cell types.Many non-exponentially degraded (NED) proteins are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
293
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(352 citation statements)
references
References 70 publications
(27 reference statements)
38
293
0
1
Order By: Relevance
“…Aneuploid chromosomes are transcribed and translated proportional to their copy number (Dephoure et al, 2014; Stingele et al, 2012; Torres et al, 2007, 2010), which can lead to stoichiometric imbalances in endogenous proteins and protein complexes (Oromendia et al, 2012; Sheltzer and Amon, 2011). To compensate, cells rely on a set of protein quality control mechanisms, including the HSF1/HSP90 folding pathway (Donnelly et al, 2014; Oromendia et al, 2012), autophagy, and proteasomal degradation (Dephoure et al, 2014; McShane et al, 2016; Santaguida et al, 2015; Stingele et al, 2012; Torres et al, 2010). The energetic cost of expressing, folding, and turning over excess proteins, as well as the downstream consequences of unmitigated protein imbalances, impose a significant fitness cost on the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Aneuploid chromosomes are transcribed and translated proportional to their copy number (Dephoure et al, 2014; Stingele et al, 2012; Torres et al, 2007, 2010), which can lead to stoichiometric imbalances in endogenous proteins and protein complexes (Oromendia et al, 2012; Sheltzer and Amon, 2011). To compensate, cells rely on a set of protein quality control mechanisms, including the HSF1/HSP90 folding pathway (Donnelly et al, 2014; Oromendia et al, 2012), autophagy, and proteasomal degradation (Dephoure et al, 2014; McShane et al, 2016; Santaguida et al, 2015; Stingele et al, 2012; Torres et al, 2010). The energetic cost of expressing, folding, and turning over excess proteins, as well as the downstream consequences of unmitigated protein imbalances, impose a significant fitness cost on the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent formation of an X-β-gal homotetramer led to the nearly (but not quite) complete cessation of the degradation of a "mature" X-β-gal tetramer by the Arg/N-end rule pathway (15,18,19). Later studies have shown that a non-first-order degradation kinetics is also a frequent aspect of proteolysis by the Ub system at large, resulting, primarily, from the same causes of time-dependent protein folding and formation of protein complexes (44,(57)(58)(59).…”
Section: Degradation Of Chk1 In Naa10δ Cells Does Not Involve the Cup9mentioning
confidence: 99%
“…In vivo half-lives of intracellular proteins range from less than a minute to many days (1)(2)(3)(4)(5)(6). The term "half-life" is, at best, an approximate descriptor of a protein's degradation curve.…”
mentioning
confidence: 99%
“…(ii) The process of conformational maturation, i.e., transitions from a newly formed, still partially unfolded (and often more vulnerable to proteolysis) monomer of a protein to its final state, either as a folded monomer or an oligomer of the homo or hetero kind. Mature proteins are usually more resistant to proteolysis, in part through steric shielding of their degradation signals (degrons) (4,5,(13)(14)(15)(16)(17)(18)(19). (iii) A variety of chemical (usually enzymatic) modifications of a protein that can change its metabolic stability either cotranslationally or posttranslationally.…”
mentioning
confidence: 99%